Complexity and Geoheritage Importance of Granite Pseudokarst from the Belaya River Gorge (Western Caucasus) - Dmitry A. Ruban (Geosciences, 2022)
New investigations in the Western Caucasus contribute to the understanding of granite pseudokarst (sensu lato) and megaclasts linked to river erosion. A plot on the bank of the Belaya River (Mountainous Adygeya, Western Caucasus) was selected to examine diverse and abundant pseudokarst features (small rock basins, hollows, potholes, and channels) and large clasts. Morphological analysis of these features clarifies their general characteristics and genetic interpretations. Pseudokarst features can be classified into two major categories, namely the relatively small (<1 m) and large (>1 m) features. Potholes, which are usually 1–3 m in size, are the most characteristic features occurring on two levels, i.e., on steep walls of the gorge (half-filled with river water) and on slightly inclined surfaces of a terrace-like landform (subaerial exposure). In both cases, their walls from the side of the river are broken. Apparently, these potholes were formed on the river bottom. Subsequent incision of the gorge elevated potholes and the river has eroded them from one side. Apparently, some pseudokarst features are related to macroturbulent flood flows and granite weathering. Due to its scientific uniqueness and aesthetic attractiveness, this granite pseudokarst constitutes geoheritage, which can be exploited for the purposes of geoscience research and geotourism development.